Chabani Manganyi: Reflecting back on the contemporary possibilities of a liberatory black psychology - Kessi, Shose (PINS-Psychology in Society, 2016)
Chabani Manganyi’s memoir, Apartheid and the making of a Black psychologist is an account of a series of seminal moments in the life of an eminent psychologist and astounding human being. The reader is taken on a journey that tells snippets of his many lives in a country ridden with untold hardships and moments of incredible victory. The versatility of Manganyi’s professional endeavours speaks to his many talents, interests and passion for human life. From his clinical and neuropsychology research; the biographies of the renowned South Africans Es’kia Mphahlele, Gerard Sekoto, and Dumile Feni; to his work in apartheid courts; and then on to higher education; Manganyi’s life and career are inspirational.